2021
DOI: 10.1080/09637486.2021.1926935
|View full text |Cite
|
Sign up to set email alerts
|

Habitual coffee and caffeinated beverages consumption is inversely associated with arterial stiffness and central and peripheral blood pressure

Abstract: Gabutti (2021): Habitual coffee and caffeinated beverages consumption is inversely associated with arterial stiffness and central and peripheral blood pressure, International Journal of Food Sciences and Nutrition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…There are no available studies investigating the association between DPs at breakfast and vascular health, but some of the DPs’ components have been previously associated with vascular biomarkers. Data regarding coffee consumption and Aix are insufficient, because there are studies in agreement with our findings [ 23 ] and studies that found an inverse association between coffee consumption and Aix [ 24 , 25 ]. The positive association of coffee consumption with Aix could be explained by the increased wave reflections caused by caffeine intake, which in turn increase Aix [ 23 ].…”
Section: Discussionmentioning
confidence: 42%
“…There are no available studies investigating the association between DPs at breakfast and vascular health, but some of the DPs’ components have been previously associated with vascular biomarkers. Data regarding coffee consumption and Aix are insufficient, because there are studies in agreement with our findings [ 23 ] and studies that found an inverse association between coffee consumption and Aix [ 24 , 25 ]. The positive association of coffee consumption with Aix could be explained by the increased wave reflections caused by caffeine intake, which in turn increase Aix [ 23 ].…”
Section: Discussionmentioning
confidence: 42%
“…Caffeine acutely increases arterial stiffness and negatively impacts vascular health in some studies, 226 , 227 while regular consumption may be inversely associated with arterial stiffness and central and peripheral BP. 233 Alcoholic beverages, such as red wine, beer, and vodka, may protect against oxidative stress-induced increases in arterial stiffness. 228 Alternatively, a recent systematic review showed that while light to moderate alcohol consumption may have minimal effects on FMD, heavy alcohol consumption is associated with a decrease in FMD.…”
Section: How Can Vascular Ageing Be Modified?mentioning
confidence: 99%
“…Moderate coffee consumption (>3 cups/day) reduces CVD risk factors such as arterial stiffness and high blood pressure [167] Randomized Controlled Trial 12 volunteers (19-39 years old) Administration of caffeine (200 mg, 12 h intervals) during sleep deprivation reduced HR and increased HF-HRV. The concentration effect was nonlinear.…”
Section: Study Type Model Results Referencementioning
confidence: 99%
“…In addition, a US follow-up study of 23,878 participants over 16 years found that the daily caffeine consumption of about 100-200 mg or >200 mg is associated with a lower risk of CVD mortality [166]. An inverse association between coffee consumption and CVD risk factors (blood pressure and arterial stiffness) was also observed in another study, showing the beneficial effect of moderate coffee consumption [167]. A similar association was observed concerning coffee consumption and hypertension risk [168].…”
Section: Cardiovascular Diseasesmentioning
confidence: 90%